The Future of the Past: How Digital Literacy Is Revolutionizing History Education - Kuntum Fitriana; Rendi Marta Agung (Proceedings Series on Social Sciences & Humanities, 2026)
This paper explores the transformative impact of digital literacy on history education in the digital age. While traditional methods often emphasize memorization of events, dates, and figures, digital literacy introduces critical thinking, interactivity, and multimedia engagement into historical inquiry. This study aims to analyze how digital tools ranging from digital archives and interactive timelines to augmented reality (AR) and social media reshape pedagogical approaches in history classrooms. Employing a qualitative descriptive method, the study gathers data through document analysis and interviews with secondary school history educators. Results indicate that digital literacy facilitates a more participatory and contextual understanding of the past, encouraging students to critically analyze sources, compare narratives, and engage in historical interpretation. These findings suggest that the future of history education lies in a digital, student-centered paradigm that promotes inquiry-based learning and digital citizenship.